Social context and depression severity and duration in Canadian men and women: exploring the influence of social support and sense of community belongingness. (3rd May 2013) - Fowler, Ken; Wareham‐Fowler, Stacey; Barnes, Caroline
Abstract: This study examined the effects of 4 types of social support and sense of community belongingness on depression severity and duration in Canadian men and women. Using the concept of social capital, it is argued that sense of community belongingness is a distal social variable, distinct from proximal social factors (e.g., types of social support). Data associated with 6, 112 respondents were extracted from the Canadian Community Health Survey (CCHS; Statistics Canada, 2002) and analyzed. Regardless of gender, higher levels of positive social interaction, and a stronger sense of community belongingness predicted less severity and shorter duration. However, very intriguing gender differences also emerged, which are discussed with reference to the reciprocity norm, conservation of resources theory, and social capital.